2004
DOI: 10.1021/ic0348897
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative XAS and X-ray Diffraction Study of New Binuclear Mn(III) Complexes with Catalase Activity. Indirect Effect of the Counteranion on Magnetic Properties

Abstract: Four new binuclear Mn(III) complexes with carboxylate bridges have been synthesized: [[Mn(nn)(H(2)O)](2)(mu-ClCH(2)COO)(2)(mu-O)](ClO(4))(2) with nn = bpy (1) or phen (2) and [[Mn(bpy)(H(2)O)](2)(mu-RCOO)(2)(mu-O)](NO(3))(2) with RCOO = ClCH(2)COO (3) or CH(3)COO (4). The characterization by X-ray diffraction (1 and 3) and X-ray absorption spectroscopy (XAS) (1-4) displays the relevance of this spectroscopy to the elucidation of the structural environment of the manganese ions in this kind of compound. Magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 48 publications
(112 reference statements)
5
28
0
Order By: Relevance
“…Although the structure of these enzymes has been determined, their catalytic mechanism is still poorly understood and the functional role of the bridges is yet unclear. Owing to their potential application as therapeutic agents against oxidative stress and as catalysts for bleaching and organic chemistry, a large number of dinuclear manganese complexes including various types of ligands have been synthesized and structurally characterized and many model complexes have been reported that show catalase activity [9][10][11][12][13][14][15][16]. An exhaustive and comprehensive review of the relevant research has recently been made [17].…”
Section: Introductionmentioning
confidence: 99%
“…Although the structure of these enzymes has been determined, their catalytic mechanism is still poorly understood and the functional role of the bridges is yet unclear. Owing to their potential application as therapeutic agents against oxidative stress and as catalysts for bleaching and organic chemistry, a large number of dinuclear manganese complexes including various types of ligands have been synthesized and structurally characterized and many model complexes have been reported that show catalase activity [9][10][11][12][13][14][15][16]. An exhaustive and comprehensive review of the relevant research has recently been made [17].…”
Section: Introductionmentioning
confidence: 99%
“…E is associated with Mn 1s transitions into p-like states with t 1u symmetry, and M is the main peak of the Mn K absorption spectrum. It has been shown that the position of the K-edge depends on the oxidation state of the manganese and the nature of the ligands [34]. The XANES analysis data for 2 are nearly same as those for 1.…”
Section: Preparation and Structures Of Complexes 1 Andmentioning
confidence: 77%
“…P is a pre-edge peak arising from a dipole-forbidden, but quadrupole-allowed, 1s ? 3d inner atomic transition in MO 5 N [34]. E is associated with Mn 1s transitions into p-like states with t 1u symmetry, and M is the main peak of the Mn K absorption spectrum.…”
Section: Preparation and Structures Of Complexes 1 Andmentioning
confidence: 99%
“…Antiferromagnetic interactions with |J| values in the range 6-15 cm À1 have been reported for Type-I [7][8][9][10][11][12][13][14][15] and Type-II [16][17][18][19][20][21][22][23] complexes. Type-V [37][38][39][40][41][42][43][44][45][46][47][48] compounds are weakly coupled with |J| $ 3 cm À1 , with both ferromagnetic and antiferromagnetic examples known. Strongest interactions occur in Type-IV compounds which are all antiferromagnetic having |J| value in the range, 90-100 cm À1 .…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…A variety of Mn(III,III) complexes differing in their core units have been reported so far (Scheme 1). The core structures and observed MnÁ Á ÁMn distances of oxo-and alkoxo-bridged dimanganese(III,III) complexes are as follows: Type-I, [Mn 2 (l-OR) 2 ] 4+ , 3.00-3.04 Å [7][8][9][10][11][12][13][14][15]; Type-II, [Mn 2 (l-RCOO)(l-OR) 2 ] 3+ , 2.91-2.94 Å [16][17][18][19][20][21][22][23]; Type-III, [Mn 2 (l-RCOO) 2 (l-OR) 2 ] 2+ , 2.85-2.87 Å [24][25][26][27][28]; Type-IV, [Mn 2 O 2 ] 2+ , 2.64-2.75 Å [29][30][31][32][33][34][35][36]; Type-V, [Mn 2 (l-RCOO) 2 (l-O)] 2+ , 3.08-3.22 Å [37][38][39][40][41][42][43][44][45][46][47][48]. The first four types form complexes with coplanar equatorial planes and parallel Jahn-Teller axes, while in Type-V complexes the Jahn-Teller axes were inclined by 27-90°.…”
Section: Introductionmentioning
confidence: 99%